Tinjauan Hukum Islam terhadap Implementasi Peraturan Daerah Tentang Pendidikan di Kabupaten Indramayu - Azzahra Auliadin; Siti Ngainnur Rohmah; Abdur Rahim (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The aim of this research is to analyze the implementation of Indramayu Regency Regional Regulation number 8 of 2015 at the Mahad Al-Zaytun Private Madrasah Ibtidaiyah in terms of Islamic law. This research uses qualitative methods with an empirical normative approach. The results of the research stated that the implementation of Indramayu Regency Regional Regulation number 8 of 2015 at the Mahad Al-Zaytun Private Madrasah Ibtidaiyah was running as it should. However, because its implementation is under the Ministry of Religion, the curriculum used is guided by the Decree of the Minister of Religion Number 184 of 2019 concerning Guidelines for Curriculum Implementation in Madrasas. The Islamic law review of the implementation of Indramayu Regency Regional Regulation number 8 of 2015 at the Mahad Al-Zaytun Private Madrasah Ibtidaiyah is related to Siyasah Dusturiyah. In the conception of education at Madrasah Ibtidaiyah, it is education that prioritizes students to have a strong belief in Allah and Islamic Sharia, united in Tauhid, have Karimah morals, have broad knowledge, high skills which are summarized in